Antifertility effect of bait containing Carica papaya L. seed powder in male lesser bandicoot rat, Bandicota bengalensis (Gray and Hardwicke) (Indian Journal of Experimental Biology (IJEB), 2021)
In rodent control exercise, after successful control with rodenticides, the surviving population often rebuild up themselves rapidly due to reduced competition and high rate of reproduction. In this context, here, we investigated the potential of papaya (Carica papaya L.) seed powder as a natural reproduction inhibitor for male lesser bandicoot rat, Bandicota bengalensis (Gray and Hardwicke) in reducing the post control population rebuild up rate. Exposure of male B. bengalensis to cereal based bait containing 2, 3 and 5% papaya seed powder for 15 and 30 days durations in bi-choice laboratory feeding tests resulted in the ingestion of total 7.14-18.15 and 13.74-41.25 g/kg body wt. of the active ingredient, respectively. Breeding performance of treated rats was 33.33 and 16.67% after treatment with 5% papaya seed powder for 15 and 30 days, respectively. Autopsy of rats immediately after treatment withdrawal revealed a significant decrease in weights of testis, cauda epididymis, seminal vesicles and prostate gland. Sperm motility, sperm viability and sperm count were found reduced and sperm abnormality increased significantly in the cauda epididymal fluid of treated rats as compared to untreated rats. The total proteins, 17β-HSD, 3β-HSD and testosterone levels were also found decreased in treated rats as compared to untreated rats. All the changes observed in treated rats showed partial or no recovery after 30 days of treatment withdrawal. The study suggests the potential of papaya seed powder in regulating fertility of male B. bengalensis which may be exploited as a component of integrated rodent pest management.